ANALISA PENGARUH KONSENTRASI aMDEA TERHADAP PENYERAPAN GAS KARBON DIOKSIDA (CO2) - Achmad Fadlih; Eka Megawati (PETROGAS: Journal of Energy and Technology, 2020)
Natural gas coming out of a well that has the same characteristics. Natural gas such as carbon dioxide (CO2) and H2S and water vapor are separated before natural gas is put into the process. This is very important because all three gases are corrosive and toxic. CO2 is an acidic gas, with the presence of water vapor will cause CO2 to be more corrosive and the freezing point of CO2 higher than methane ie the freezing point of CO2 is -56 ° C which will later cause blockages in the heat exchanger tubes (5E-1) whose temperature can reach -150 ° C. Methyldiethanolamine is a clear, colorless or pale yellow liquid with an ammonia odor. Methyldiethanolamine dissolves with water, alcohol and benzene. The study uses correlation and regression analysis methods that aim to see how influential the concentration of aMDEA is in absorbing CO2. Data analysis uses regression equations and coefficient of determination. Based on observations obtained that the effect of aMDEA concentration on CO2 absorption is fairly weak or has little effect because the coefficient of determination is 0.0012 or 1.2% which indicates that the relationship is very weak or has little effect.